(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The transient population dynamics is the short-term behaviour of the population structure or the response of a model to changes in its parameters. This paper investigates transient sensitivity analysis of a density dependent mathematical model of a weed species for the purpose of short- term weed control plans as an alternative to sensitivity analyses of the steady-state equilibrium that rely on long-terms dynamics of the weed population. The analysis’ result shows that the transient population growth is more sensitive to seedling survival (e) than germination rate ( ). Hence, weed population control could be targeted at seed germination and seedling stages of the weed growth for effective control plan